CD4 expression controls epidermal stem cell balance - Nadine Brandes; Heidi Hahn; Anja Uhmann (Scientific Reports)
Abstract The balance of stem cell populations is essential for the maintenance, renewal, and repair of the mammalian epidermis. Here, we report that CD4, which is a typical marker of helper T cells, monocytes, macrophages, and dendritic cells, is also expressed on murine K5+ keratinocytes. Lineage tracing of CD4+ cells reveals that their epidermal progeny has self-renewal abilities and clonogenic potential. The progeny of CD4+ epidermal cells contributes to epidermal renewal and progressively colonizes the interfollicular epidermis and hair follicles with age, thereby developing to all epidermal lineages. Wound healing studies furthermore show that the progeny of CD4+ epidermal cells accumulates at wound sites. Finally, using CD4 knockout mice we demonstrate that CD4 expression is essential for maintaining fast-cycling epidermal stem cells during homeostasis and that CD4 loss mitigates the age-related decline in wound repair capacity. Collectively, our data support the conclusion that CD4 expression is required for long-term maintenance of the epidermal stem cell balance.